Pengaruh Target Penerimaan Pajak, Realisasi Pajak dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak - Adi Sofyana Latif; Sapta Setia Darma; Rananda Septanta; Rijal Arslan (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Taxpayer compliance is a crucial factor in achieving optimal tax revenue and supporting sustainable government financing. However, differences between tax targets, realization, and enforcement mechanisms often raise questions regarding their influence on individual taxpayer compliance. This study aims to examine the effect of tax revenue targets, tax realization, and tax sanctions on individual taxpayer compliance. The research employs a quantitative approach using a survey method. The study was conducted at the South Jakarta Tax Office, with individual taxpayers who consistently paid taxes on time as the research subjects. The observation period spans five years, from 2019 to 2024. A simple random sampling technique was applied, resulting in 109 respondents. Primary data were collected through the distribution of structured questionnaires using a Likert scale. The data were analyzed using EViews version 9 with multiple linear regression analysis. The results indicate that, partially, tax revenue targets have a significant effect on taxpayer compliance, while tax realization and tax sanctions do not have a significant effect on taxpayer compliance. However, simultaneous testing reveals that tax revenue targets, tax realization, and tax sanctions collectively have a significant effect on taxpayer compliance. These findings suggest that strategic tax target setting plays a more influential role in encouraging compliance compared to realization outcomes and sanction policies.